2020
DOI: 10.3390/ani10101852
|View full text |Cite
|
Sign up to set email alerts
|

Low-Protein Diet Supplemented with Medium-Chain Fatty Acid Glycerides Improves the Growth Performance and Intestinal Function in Post-Weaning Piglets

Abstract: Medium-chain fatty acid glycerides have been shown to provide energy for rapid oxidation in the body. The study was conducted to investigate the effects of dietary supplementation with medium-chain fatty acid glyceride on the growth performance and intestinal health of weaned piglets fed with a low-protein diet. Nighty healthy weaned piglets were randomly divided into five treatments: NP (Normal protein treatment, normal-protein diet no antibiotics included); NC (Negative control, low-protein diet no antibioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 37 publications
(37 reference statements)
1
20
1
Order By: Relevance
“…The experiment lasted for 14 days. The growth performance of piglets was also presented in the previous study that no differences in average daily gain and feed/gain ratio among all treatments were observed ( 3 ).…”
Section: Methodsmentioning
confidence: 65%
See 2 more Smart Citations
“…The experiment lasted for 14 days. The growth performance of piglets was also presented in the previous study that no differences in average daily gain and feed/gain ratio among all treatments were observed ( 3 ).…”
Section: Methodsmentioning
confidence: 65%
“…Treatments were as follows: NP (Normal protein, normal-protein diet no antibiotics included); NC (Negative control, low-protein diet no antibiotics included); PC (Positive control, low-protein diet +75 mg/kg quinocetone, 20 mg/kg virginiamycin and 50 mg/kg aureomycin); MCT (low-protein diet + tricaprylin + tricaprin); GML (low-protein diet + glycerol monolaurate). The compositions and nutritional levels of the diet were presented in the previous study ( 3 ). The medium-chain fatty acid glycerides were obtained from Deyuanshun Biological Technology Co., Ltd. (Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The small intestine is the main site for protein digestion and absorption and is also an important immune organ. Therefore, the maintenance of intestinal health could influence the growth performance ( 5 ) and immune status ( 6 ) of pigs. Lan et al.…”
Section: Introductionmentioning
confidence: 99%
“…The small intestine is the main site for protein digestion and absorption and is also an important immune organ. Therefore, the maintenance of intestinal health could influence the growth performance (5) and immune status (6) of pigs. Lan et al (7) suggested that high protein (HP) diets led to lower ileal and colonic indices in rats related to the mucosal immune response.…”
Section: Introductionmentioning
confidence: 99%